Injury History and Attentional Focus Disruption in Sanda Competitions at a Sports Institute in China - Huang, Ran (Pacific International Journal, 2025)
This study investigates the relationship between injury history and attentional focus disruption in Sanda athletes from Wuhan Sports University. Recognizing that injuries in this high-intensity combat sport extend beyond physical damage to potentially impair cognitive functions critical for performance, a descriptive-comparative-correlational design was employed. Fifty-two athletes completed a validated questionnaire assessing their injury profiles and competition distractibility. Results indicated that while upper limb injuries were common, their overall severity was manageable. The primary triggers for attentional disruption were auditory and situational factors, such as an opponent’s coach’s instructions or self-error, which predominantly impacted decision-making rather than technical execution. Interestingly, no significant overall correlation was found between the composite measures of injury history and distractibility. However, nuanced analysis revealed that specific injury factors, like recurrence patterns and location, could influence coping strategies and attentional recovery, with years of training also affecting distraction timing. These findings suggest that the injury-attention dynamic is complex and not merely linear. Consequently, the study recommends integrated interventions, including preventative training to reduce injury recurrence, structured mental skills coaching to bolster focus, and personalized rehabilitation protocols. Establishing a monitoring system for injury patterns and cognitive performance is essential to optimize the holistic readiness of Sanda athletes, ensuring both their physical safety and cognitive sharpness in competition.